The spectralism of Gerard Grisey: from the nature of the sound to the nature of listening - Humięcka-Jakubowska, Justyna (Interdisciplinary Studies in Musicology, 2018)
The paper is an attempt to consider Grisey’s music from an ontological perspective, not only as a cultural product, but above all as an entity derived from the order of nature. The spectral music, as an entity derived from the order of nature, may be studied primarily as mental reality that refers directly to the composer’s stance, physical reality, that refers to the material from which the music is produced, and psychological reality of relating to its perception. In Grisey’s creative attitude, one distinguishes several tendencies. The article describes treating sound as a living organism in time, replacing the idea of timbrematière, from the traditional art of orchestration, with timbre-son, based on the science of acoustics, a processual approach to time and form, taking account in the creative process of human perceptual abilities and seeking a musical language based on scientific premises. These tendencies are described in the context of the composer's statements and examples of his work. Taking the nature of sounds as his starting point, Grisey headed towards the nature of listening, and the effects of this journey are his clearly specified views and their manifestation in composed musical works.